Why We Should Abandon the Semantic Subset Principle. Issue 1 (2nd January 2019) - Musolino, Julien; Laity d'Agostino, Kelsey; Piantadosi, Steve
ABSTRACT: In a recent article published in this journal, Moscati and Crain (M&C) showcase the explanatory power of a learnability constraint called the Semantic Subset Principle (SSP) (Crain et al. 1994 ). If correct, M&C's argument would represent a compelling demonstration of the operation of an innate, domain specific, learning principle. However, in trying to make the case for the SSP, M&C fail to clearly define their hypothesis, omit discussion of key facts, and contradict the theory itself. Moreover, their presentation does not address the core arguments and alternatives against their account available in the literature and misrepresents the position of their critics. Once these shortcomings are understood, a very different conclusion emerges: its historical significance notwithstanding, the SSP represents a flawed and obsolete account that should be abandoned. We discuss the implications of the demise of the SSP and describe more powerful and plausible alternatives that provide a better foundation for ongoing work in language acquisition.